Healthy ageing in a deprived northern UK city: A co‐creation study. (22nd May 2020) - Glover, Lesley; Dyson, Judith; Cowdell, Fiona; Kinsey, Debbie
Abstract: With ageing comes an increased risk of poor health and social isolation, particularly in poorer populations. Older people are under‐represented in research and as a result interventions may not take account of their context or barriers to participation. In co‐creative work, future service users work with professionals on an equal basis to design, develop and produce a service or intervention. Our objectives were to (a) undertake a co‐creation study with older people living in a northern city in the United Kingdom, (b) explore maintenance of health and well‐being in older age, (c) explore the application of co‐creation with an older community population and (d) evaluate the process and inform future work. The study was conducted during 2017 by a project team of 10 lay community dwelling older people and four university researchers. Findings demonstrate that state of mind and of health were key to well‐being in older age. Feeling safe, comfortable and pain free were important along with being able to adapt to change, have choice and a sense of personal freedom. Social connectedness was seen as the keystone to support healthy behaviours. Rather than developing new interventions, there was a perceived need to connect people with existing resources and provide a human 'bridge' to address barriers to accessing these. In conclusion, the co‐creation process proved productive, even when undertaken on a small scale. The scope of the project needs to be realistic, to use diverse methods of recruitment and skilled facilitators, and to prepare well in terms of accessibility, simple systems and appropriate information provision.